INDEKS KEANEKARAGAMAN BIOTA PERAIRAN SEBAGAI INDIKATOR BIOLOGIS PENCEMARAN LOGAM BERAT DI PERAIRAN PANTAI BITUNG, SULAWESI UTARA - Dolfie Mokoagouw (EKOTON, 2013)
In industrial activity, the heavy metals are highly used to develop and increase their products. Utilization of heavy metals as catalyst, product and by-product produced pollutant of the heavy metals around Bitung Municipality coastal areas. The objective of this study was to evaluate the impact of the heavy metal industrial activity indicated by biological method on farmer’s social economic and community around Bitung Municipality coastal areas. This research was conducted from May 1999 to January 2000 using eleven samples of locations around Bitung Municipality coastal areas. Samples were taken once every two weeks at each location and analyzed at the laboratory. Survey of the farmer’s social economic was conducted after defining the laboratory data of heavy metal contents. The results of this study showed that diversity indexes of the benthic fauna were 0.33 to 2.79. Main parts of the locations from St. 2 to St. 11 showed diversity indexes of plankton of 1.12 to 3.14. During observation, there were about 48 planktons. Diversity index of shells ranged from 0 to 1.79; similarly, those of fish ranged from 0 to 2.43. Many of those index laid at the above of 2. The results of this study can be concluded that industrial activities around Bitung municipality coastal areas have contaminated the heavy metal pollutants in the bodies of marine animal organisms such as, benthic fauna, plankton, fish and shells varied among eleven locations.